Hofmeyr
XII, 258 p. 104 illus., 82 illus. in color.
Keywords: This edited volume provides the historical and geological background, as well as the details pertaining to the morphology and morphometric assessments, of a singular human cranial specimen from the Late Pleistocene discovered in Hofmeyr, South Africa. The chapters are divided into 4 main sections. Section 1 discusses the discovery and historical context of the skull, while section 2 addresses its geological and geochronological contexts through dating and stable isotope analyses. Section 3 details the general morphological and morphometric analyses (description, 3-D reconstruction, morphological comparisons), and section 4 details the specific morphological analyses performed (inner ear, dentition, endocranial morphology and size). The volume will be of interest to professional and student paleoanthropologists interested in the later phases of human evolution. .